Nog steeds geslote eredienste? Deel l - Wyk, I. W. C. van (Hervormde teologiese studies, 1994)
Should church services still be closed? Part 1 This paper - in two parts - deals with the question of whether the Nederduitsch Hervormde Church should continue being a church for white persons only. The auther argues that this practice is not according to biblical teachings, and at the same time, that it will be unwise to continue it under the future sociopolitical circumstances in South Africa. He therefore calls on the Nederduitsch Hervormde Church to abandon this practice as it will bring the church into conflict with its own theological tradition.